(untitled) (Al-Academy, 2019)
The present research aims at revealing the advertising image semiotics in the American printed poster by following the image’s significance and its transformations through the poster design trends and indicating its nature whether it is an explicit or implicit image. The limits of the research were the American printed poster during 2016-2018 period. The theoretical side was determined by two sections, the first: (the advertising image semiotics) and the second (design trends in the printed poster). The research procedures were represented by the research method adopted in the analysis of the sample models identified in four models taken from the research community which contains (24) models. The selection was made according to the trend and type of the mark and then analyzed according to a research tool whose paragraphs were bases taken from the theoretical framework. After analyzing the models that represent the research sample, the researcher reached at a set of results and conclusions and the most prominent of these were that ( the designers aimed at topics devoted in the collective memory such as the pigeon, olive branch, umbrella and freedom statute as part of the act of communication and the communication theory which the designer does not find difficult to convey), in accordance with the subject of his research in light of the focus on the advertising image based on the mark logic and his analysis of the semiotics of that image.